Peran Masjid Sebagai Lembaga Pendidikan Islam Nonformal Bagi Masyarakat Muslim Pedan (Studi Di Masjid Al-Jalal Gatak, Kedungan, Pedan, Klaten Tahun 2016) - Luthfatul Janah, Nafis, Drs. Marpuji Ali, M.SI (2016)
In Islamic education entails an educational environment in order to achieve educational goals. There are three main educational environments, they are family, school, and community. The mosque was one means of non-formal education for the people of Islam. The existence of Al-Jalal mosque as a Muslim community center in the District Pedan at least is able to provide its own color, especially one in the field of Islamic education. The mosque is managed by management mosque and Leader of Muhammadiyah Branch (LMB) Pedan, used as a center of da'wah amar ma'ruf nahi munkar as well as a Muslim community center in the Pedan District. Based on this background, the formulation of the problem in this research is "What is the role of Al-Jalal mosque at Pedan as non-formal Islamic education institution for Pedan Muslim communities?". Therefore the purpose of this study is to describe the role of Al-Jalal mosque at Pedan as non-formal Islamic education institution for Pedan Muslim communities. The benefits of this research are to contribute ideas on how the role of the mosque as Islamic non-formal educational institutions. In addition, it can provide a stimulus for further research. So that the review process will continue and gain maximum results. This research was a case study and field research, with qualitative approach. Data are obtained by interview, observation, and documantation. The method of data analysis is inductive consisting of data reduction, data presentation, and conclusion. Based on the result of the research, it can be concluded that: 1) Both Mosques Management and LMB are able to make the Al-Jalal mosque as a nonformal educational institutions implementing the Islamic values in its activities. 2) The role Mosques Management with implementing main non-formal educational primarily to meet the needs of mental-spiritual people which includes: a) Holding tahsin to the people. b) Special recitation Mosques Management every Saturday Wage night c) PAE Baitul Jalal to achieving future generations of Muslims. 3) Average LMB Pedan role of non-formal Islamic education includes: recitation Sunday morning, recitation physical and spiritual health, recitation toward of break fasting, the role of the mosque in the social field includes blood donation, mass circumcision and social events. LMB role complementing the role of the Mosques Management so, not only focused on the mental-spiritual but also adds physical needs and socio-environmental material to the pilgrims so as to creating non-formal educational that was able to meet the needs of the Muslim community Pedan. So between Mosques Management and LMB are complementary in serving the public.